Feasibility of Natural Indicators Worksheets for 11th grade Student - Al Mu’min, Muhammad Ridhwan; Hairida, Hairida; Masriani, Masriani (Universitas Pendidikan Mandalika, 2023)
This study aims to determine the level of eligibility of worksheets for natural indicators of acid-base 11th grade Senior High School (SMA/MA) students in even semester. The population used in this study is a population sample consisting of six validators consisting of two content validator validators, two linguistic validator validators, and two graphic feasibility validators. Data collection instruments used were content eligibility questionnaire, linguistic feasibility questionnaire, and graphic eligibility questionnaire. The data analysis technique used is Gregory. Results Processing data in terms of content eligibility has a validity of 1 so that it has a very high level of content eligibility. For language eligibility, continued validity is obtained at 1 so that the level of language eligibility is also very high. However, the validity of the worthiness of the graphic is only 0.5 so that the level of feasibility of the graphic is still categorized as moderate. Thus, it can be concluded that LKPD of the natural indicators of acid-base for 11th grade students in even semester is feasible to be used in the learning process with very high criteria for content and linguistic aspects and moderate categories for graphic aspects.